Etiology of Cleft Lip and Cleft Palate - Pongsupot, Siritida; Ritthagol, Wipapun (Thai Journal of Orthodontics, 2020)
Cleft lip and/or cleft palate is one of the most common orofacial developmental deformities seen worldwide. Patients with this condition confront not only impaction to oral health but also esthetic and quality of life issue. There were some attempts to find etiology of cleft lip and/or cleft palate and found that genetic and environmental factors are the most important etiologic factor. Many studies showed relationship between environmental risk factor of mother exposure such as drinking alcohol, smoking, using teratogenic drugs during first trimester and working in hazardous environment and deficiency of folic acid. According to genetic factor, over 50% of cleft lip and/or palate patients were classified in non-syndromic group, while about 30% of patients were classified in syndromic group. So, genetic risk factor identification and genetic counselling were important for reduction the incidence of cleft lip and/or cleft palate and being a primary prevention for the next child birth planning.